Closure of Transsplenic Access Tracts Using Tract Embolics: Success, Clinical Outcomes, and Complications in a Tertiary Center - David Rigual; Isaac Chen; Dustin L. Roberts; James Sayre; Ravi Srinivasa (Journal of Clinical Interventional Radiology ISVIR)
Purpose The aim of the study was to evaluate the safety and effectiveness of transsplenic venous access closure. Materials and Methods Twenty patients (mean age: 51.8 years; range: 28–72), underwent 21 transsplenic venous access procedures over 4 years in this retrospective study. Comorbidities, active hemorrhage, anticoagulation, coagulation parameters, platelets, indications for transsplenic access, needle gauge, sheath size, variceal embolization method, tract embolization method, bleeding complications, and transfusion requirements and additional procedures to manage bleeding complications were recorded. Results Preprocedure comorbidities included portal hypertension (n = 18/20, 90%), portal vein thrombosis (n = 14/20, 70%), hemorrhage (n = 6/20, 30%), splenic vein thrombosis (n = 7/20, 35%), anticoagulation (n = 2/20, 10%), and sinistral portal hypertension (n = 2/20,10%). Mean baseline international normalized ratio was 1.3 (range: 1–1.9), platelets 122 (range: 18–492). Most common transsplenic access indications were gastric varices with nonpatent portosystemic shunt (n = 11/21, 52%) and portal vein targeting for transjugular intrahepatic portosystemic shunt (n = 8, 38%). Most common access sheath sizes were 4-French (n = 5, 24%) and 6-French (n = 6, 29%). Fifteen procedures (71%) involved variceal embolization. Transsplenic tracts were embolized with microfibrillar collagen alone (n = 7), coils and microfibrillar collagen (n = 8), or others (n = 6). Based on the Society of Interventional Radiology adverse event classification system, embolization complications included one major (splenic artery pseudoaneurysm and a splenic vein pseudoaneurysm) and three moderate (19%) adverse bleeding events, which required blood transfusion. Conclusion Transsplenic venous access tract embolization is a safe and moderately effective method to achieve tract hemostasis, with an overall clinical failure rate of 20%.